Management of Congenital Duodenal Obstruction by Diamond-Shaped Duodenoduodenostomy - Mahmood Mosa Mahmood; Alaa Mohammed Ali Al Baazi; Athir Ahmed Kadium (Institute of Medico-legal Publications Pvt Ltd, 2021)
A prospective study of 20 patients with clinical diagnosis of duodenal obstruction done at pediatric surgery center in AL Khanssa maternity and children Teaching Hospital in Mosul from December 2006-January 2010, a detailed case-record of 20 consecutive newborn patients treated for duodenal obstruction. The aims of the study was to analyze our experience and to evaluate the clinical presentation, diagnosis, postoperative care, and outcome in infants with duodenal obstruction.The 20 patients were classified according to classification system modified from James A. O’Neill: duodenal web, atresia , annular pancreas and malrotation.The presumptive diagnosis and decision regarding the need for surgery was based on clinical findings and investigation of plain abdominal radiographs in all patients without the need of dye study. Abdominal ultrasound examination was done for all patient to evaluate the associated renal anomalies and echocardiogram was done for 15 patients because of suspicion of congenital heart disease.other laboratory investigation including complete blood count, serum electrolyte, blood urea and total serum bilirubin were done for all patients.the management strategy for all patients was outlined as follows: After initial evaluation, a nasogastric tube (NGT) was placed for gastric decompression. The operative procedures performed through supra umbilical transverse abdominal incision. The type of duodenal obstruction was assessed after mobilizing the ascending and transverse colon to the left and identifying any associated malrotation. Kocherization of duodenum then performed and a transpyloric tube was passed to determine if a windsock abnormality was present . In duodenal atresia intraoperatively injection of saline or air into the distal segment was done to rule out a second atresia. Using a single layer of interrupted suture with posterior knots tied inside and anterior knots tied outside by using 5-0 or 6-0 Vicryl (polyglactin) o Polydiaxonone suture(PDS) 5/0 to complete the anastamosis. The age of our patients were ranging from1day to 16 days and divided in to two groups from 1 up to 7 days. The Common clinical findings in our patients were bilious emesis, upper abdominal distension, failure to pass meconium . And accordingly the incidence of each symptoms and signs.The available investigations in our center at any time was the plain abdominal x ray, the finding in plain x-ray of abdomen was double bubble sign in 18(90%)of the patients and single gastric gas shadow in 2(10%) of patient. Abdominal ultrasound examination was done for all patients locking for any associated anomalies especially of the urinary tract. The finding was ectopic kidney in 1(5%) and hydronephrosis in 1(5%) of our patient. Echocardiography has been performed in 15 patients , abnormal in 2 male babies one of them had VSD and another one had ASD. Careful examination and follow up locking for associated anomalies were done and their types and percentile shows male patient have more associated anomalies than female.